2018
DOI: 10.11591/ijece.v8i6.pp4230-4238
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Grayscale Template Matching for Saudi Arabian Riyal Paper Currency Recognition

Abstract: <p>Detecting the authenticity of paper currencies using automated based Paper Currency Recognition (PCR) with image processing techniques was still a hot topic of discussion, due to the circulation of counterfeit currency that was still overwhelming in some countries. There was a downside along with this advancement in technology in the field of color printing, duplication, and scanning, because it was became one of the supporting factors of the increasing crime rate in production of counterfeit money. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The author in [13] scanned 110 banknotes representing 8 denominations of the fourth issue of the Saudi Arabian currency. The authors in [14] demonstrated a paper currency recognition and classification for the old fifth issue of the Saudi Arabian banknote by collecting 100 samples of the following denominations: 1, 5, 10, and 50 Saudi Arabian Riyals. The authors in [15] presented a banknote recognition software for various currencies, including the Saudi Arabian currency.…”
Section: Related Workmentioning
confidence: 99%
“…The author in [13] scanned 110 banknotes representing 8 denominations of the fourth issue of the Saudi Arabian currency. The authors in [14] demonstrated a paper currency recognition and classification for the old fifth issue of the Saudi Arabian banknote by collecting 100 samples of the following denominations: 1, 5, 10, and 50 Saudi Arabian Riyals. The authors in [15] presented a banknote recognition software for various currencies, including the Saudi Arabian currency.…”
Section: Related Workmentioning
confidence: 99%